AATF/Che-1—An RNA Binding Protein at the Nexus of DNA Damage Response and Ribosome Biogenesis - Kaiser, Rainer W. J.; Erber, Johanna; Höpker, Katja; Fabretti, Francesca; Müller, Roman-Ulrich (Frontiers in Oncology, 2020)
The DNA damage response (DDR) is a complex signaling network that is activated upon genotoxic stress. It determines cellular fate by either activating cell cycle arrest or initiating apoptosis and thereby ensures genomic stability. The Apoptosis Antagonizing Transcription Factor (AATF/Che-1), an RNA polymerase II-interacting transcription factor and known downstream target of major DDR kinases, affects DDR signaling by inhibiting p53-mediated transcription of pro-apoptotic genes and promoting cell cycle arrest through various pathways instead. Specifically, AATF was shown to inhibit p53 expression at the transcriptional level and repress its pro-apoptotic activity by direct binding to p53 protein and transactivation of anti-apoptotic genes. Solid and hematological tumors of various organs exploit this function by overexpressing AATF. Both copy number gains and high expression levels of AATF were associated with worse prognosis or relapse of malignant tumors. Recently, a number of studies have enabled insights into the molecular mechanisms by which AATF affects both DDR and proliferation. AATF was found to directly localize to sites of DNA damage upon laser ablation and interact with DNA repair proteins. In addition, depletion of AATF resulted in increased DNA damage and decrease of both proliferative activity and genotoxic tolerance. Interestingly, considering the role of ribosomal stress in the regulation of p53, more recent work established AATF as ribosomal RNA binding protein and enabled insights into its role as an important factor for rRNA processing and ribosome biogenesis. This Mini Review summarizes recent findings on AATF and its important role in the DDR, malignancy and ribosome biogenesis.